Gross Pollutant Traps: Wet Load Assessment at Sungai Kerayong, Malaysia - Mohd Shah M.R.; Zahari N.M.; Md Said N.F.; Sidek L.M.; Basri H.; Md Noor M.S.F.; Mohammad Husni M.M.; Jajarmizadeh M.; Roseli Z.; Mohd Dom N. (Institute of Physics Publishing, 2023)
Catchments; Pollution; Rivers; Runoff; Storm sewers; Urban planning; Economic transformation; Effective management; Gross pollutants; Main rivers; Malaysian governments; Planning tools; Residential areas; Stormwater quality control; River pollution; anthropogenic source; catchment; pollutant source; pollution control; pollution monitoring; quality control; residential location; stormwater; transform; urban area; urbanization; water pollution; Gombak River; Jinjang River; Kedah; Klang River; Klang Valley; Malaysia; Sungai Batu; West Malaysia